The Problem of Continuity of Identity in the Context of Intergenerational Dialogue - Simonyan, Hamlet (Bulletin of Yerevan University E: Philosophy, Psychology, 2023)
With the endless socio-cultural transformations taking place in the modern world, people’s notions and beliefs are also changing, people’s value system is being reorganized, new challenges and new priorities to face them, completely different from the previous ones, and often negating, appear. Instantaneous changes that cause cultural traumas to social systems, the inevitable prospect resulting from globalization processes and leading to the standardization of cultures and generally human existence dissolve and eliminate the characteristics of collective identity without any extra effort. The situation becomes more intense when the issue of passing national identity on to future generations comes out; a circumstance that implies making sense of the past experience, mastering the present and building a sustainable future. In such circumstances, when the discourse of continuity of identity faces such complications, proper intergenerational dialogue becomes one of the guarantees of the constructivity and stability of social systems. The article analyzes the problem of continuity of national identity in the context of intergenerational relations, referring to the inclusion of past life experiences in postfigurative, cofigurative and prefigurative cultures. Based on the equivalent models of intergenerational relationships in the above-mentioned cultures, the article also addresses the vertical (temporal) and horizontal (spatial) dimensions of identity. The importance of intergenerational solidarity and constructive dialogue between generations, as well as some practical examples related to the topic are discussed.